Empowerment of Earthquake Victims in Bekasi through Legal Approaches and Community Service - Tjandraningsih Dewi (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2025)
The earthquake that struck Bekasi has caused serious impacts on the social, economic, and legal rights of the affected community. The purpose of this study is to examine and implement the empowerment of earthquake victims in Bekasi through legal approaches and community service in order to enhance their resilience and protect their rights. The methods employed include literature review, field observation, and the implementation of community service programs oriented toward legal education and access to justice. The results indicate that empowerment through legal approaches strengthens victims’ understanding of their legal rights and increases their participation in the recovery process. In addition, community service fosters an environment that supports community resilience and self-reliance in overcoming the disaster. The study concludes that synergy between legal approaches and community service is an effective strategy to accelerate recovery and empowerment of earthquake victims in Bekasi, thereby contributing to the creation of a more resilient and sustainable society.